Developing a three stream, mixed flow variable cycle engine in NPSS - Larsson, Vincent (My University, 2023)
One of the more important areas of improvement in aircraft engines is fuel efficiency for economicas well as environmental reasons. While modern civil turbofan engines are primarily designed with fuel efficiency in mind, thus having very high bypass ratios, military engines need to uphold high specific thrust requirements in order to reach supersonic speeds as well as perform the manoeuvres sometimes necessary in a combat scenario. Modern military aircraft engines are therefore designed as low-bypass turbofans capable of producing significant specific thrust, but at the cost of having a high specific fuel consumption even at lower speeds in comparison to their civil counterparts. The variable cycle engine, or adaptive cycle engine, is an engine concept for which the engine cycle can be modified in-flight to better fulfil different mission requirements. The type of variable cycle engine of interest for this thesis is a so called three stream, double bypass, mixed-flow variable cycle engine, in which a low-bypass turbofan engine has had an additional outer bypass duct added to it. This third stream can be independently modulated to vary the bypass ratio of the engine during flight, increasing the airflow through the bypass duct during subsonic flight for better fuel efficiency and increasing the flow through the engine core during supersonic flight for higher thrust. For the thesis, the Numerical Propulsion System Simulation software (NPSS) was used to both model and simulate two variable cycle engines with differing design bypass ratios. In order to evaluate the models, a baseline model representing a generic, standard low-bypass turbofan engine was also modelled for comparison. The primary area of study for the models was the effect of increased bypass ratio on thrust specific fuel consumption at different altitudes and speeds, as well as the total fuel savings during a simulated mission. The results showed that overall, the variable cycle engines had an advantage over the standard engine with regard to fuel consumption during dry-thrust. The mission analysis performed showed possible fuel savings of ca. 11 and 14 % compared to the base model for the two VCE designs respectively. This came however at the expense of a lower maximum net thrust when operating at wet-thrust settings.